PENINGKATAN KETERAMPILAN BERBICARA SISWA DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL DI KELAS V SEKOLAH DASAR - Trisnadewi, Vidia; Halidjah, Siti; Margiati, K.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTrisnadewi, Vidia. 2018. Improving Student Speaking Skills by Using Audio Visual Media in Vocational Class of Pontianak City Primary School. Essay. Primary School Teacher Education Study Program. Department of Primary Education, Faculty of Teacher Training and Education, University of Tanjungpura Pontianak. Advisor (I) Dr. Hj. Siti Halidjah, M.Pd., and Supervisor (II) Dra. K.Y. Margiati, M.Si.The common problem of this research, "Is the use of audio-visual media can improve the speaking skills of students in Class VC Elementary School 03 Pontianak City?" This study aims to improve students' speaking skills by using audio visual media at VC students Elementary School 03 ontianak Kota . The research method is descriptive method and the form of research is classroom action research with collaborative nature. The place of this research is at State Elementary School 03 Pontianak City. Subjects of teachers and all students of VC class of 31 people. Data collecting technique used is direct observation and document observation with tool in the form of observation sheet and document observation sheet. This research was conducted in 3 cycles with the final result of research on relevant content aspect, systematic organization, word accuracy and smoothness obtained in cycle I 10,72% in cycle II 67,85% and at cycle III 75%. Based on the data obtained can be concluded there is an increase in each cycle.Â Keywords: Improved, Speaking Skills, Audio Visual Media.Â